2003
DOI: 10.1167/iovs.03-0037
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Localization of Neurotrophins and Neurotrophin Receptors in Rat Lacrimal Gland

Abstract: Members of the neurotrophin family of growth factors and their receptors are present in rat lacrimal gland, which suggests a role for NTs and their receptors in the lacrimal gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 38 publications
0
43
0
1
Order By: Relevance
“…The observed positivity of TrkB in myoepithelial cells at 30L could be related to the regulation of the contractile function of these cells and may be regulated by neurotrophins as they do in lacrimal glands (Ghinelli et al 2003).…”
Section: Discussionmentioning
confidence: 85%
“…The observed positivity of TrkB in myoepithelial cells at 30L could be related to the regulation of the contractile function of these cells and may be regulated by neurotrophins as they do in lacrimal glands (Ghinelli et al 2003).…”
Section: Discussionmentioning
confidence: 85%
“…The anti-NTRK3 antibody was raised against an epitope from the porcine NTRK protein (GenBank P24786 AAs 770-820) showing 100% homology to rat NTRK3. Western blots against rat tissues (Ghinelli et al 2003, Lazar et al 2004 show only NTRK3 brands. Briefly, 3 mm sections were deparaffinized, rehydrated through a graded ethanol series, boiled in sodium citrate (used only in neonatal NT3 immunohistochemistry), quenched in 3% hydrogen peroxide/20% methanol and 0.1% Triton-X solution, and then blocked with 10% goat serum (normal goat serum; Vector Laboratories, Inc., Burlingame, CA, USA) for 20 min prior to incubation with primary antibody for 12 h. Sections were then incubated in 0.1% Triton-X solution again (not used in neonatal NT3 protocol), washed in PBS and incubated with 1:300 diluted biotinylated secondary antibody for 20-40 min (goat anti-rabbit IgG; Vector Laboratories, Inc.), washed, and incubated with streptavidin peroxidase (Zymed, San Francisco, CA, USA) prior to colour development with a DAB peroxidase substrate kit (Vector Laboratories, Inc).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The cornea and the conjunctival layer show an ability not only to produce and release NGF, but also to express tropomycin trk A tyrosine kinase receptor (trkA NGFR ) and p75 pan-neurotropin rececptor (p75 NTR ), essential for mediation of the biological activities of NGF [11,12]. NGF, trkA NGFR , and p75 NTR are expressed by lacrimal gland tissue, suggesting that NGF may have a role in the maintenance of the tear film, regulating the functions of both cornea and conjunctiva [13][14][15]. It has been reported that NGF has a specific role in ocular surface inflammation associated with dry-eye syndrome [16].…”
Section: Introductionmentioning
confidence: 99%